Geometry in our three-dimensional world - Posamentier, Alfred S. 1942-; Thaller, Bernd 1956-; Dorner, Christian; Geretschläger, Robert 1957-; Maresch, Günter; Spreitzer, Christian 1979-; Stuhlpfarrer, David ca. 20./21. Jh (World Scientific, 2022)
"The book presents a comprehensive overview of various aspects of three-dimensional geometry that can be experienced on a daily basis. By covering the wide range of topics - from the psychology of spatial perception to the principles of 3D modelling and printing, from the invention of perspective by Renaissance artists to the art of Origami, from polyhedral shapes to the theory of knots, from patterns in space to the problem of optimal packing, and from the problems of cartography to the geometry of solar and lunar eclipses - this book provides deep insight into phenomena related to the geometry of space and exposes incredible nuances that can enrich our lives. The book is aimed at the general readership and provides more than 420 color illustrations that support the explanations and replace formal mathematical arguments with clear graphical representations"--
Keywords: Dreidimensionale Geometrie; Unterhaltungsmathematik; Geometry, Solid; Polyhedra; Three-dimensional modeling